Effects of transparent online open procurement on prices, volumes, and costs of medicines: an interrupted time series study in Ningxia, China - Jingying Gao; Chaojie Liu; Yinming Li; Xizhuo Chen; Tianqin Xue; Yuqing Tang; Yuqing Tang; Yuqing Tang (Frontiers Media S.A., 2024)
ObjectivesTo assess the effects of the transparent online open procurement arrangement on the prices, volumes, and costs of medicines in Ningxia, China.MethodsData were extracted from the Ningxia pharmaceutical procurement platform, covering 16 months of purchase orders (December 2019 to March 2021) prior to the implementation of the transparent online open procurement policy and 20 months of purchase orders after the implementation of the policy (April 2021 to November 2022). Interrupted time series (ITS) analysis was performed to evaluate the effects of the transparent online open procurement policy on the prices, volumes, and total costs of the purchase orders.ResultsAfter implementation of the transparent online open procurement policy, the average price of purchased medicines showed a declining trend by 0.012 Yuan per month, while the total volume of purchase orders declined at a rate by 1.741 million per month measured by the smallest formulation units and the total costs of the purchase orders decreased at a rate by 5.525 million Yuan per month.ConclusionThe transparent online open procurement policy resulted in reduced prices, lowered volumes, and lowered total costs of purchased orders of medicines.